Design and Amazonian nature: An illustrative study on commercial fruits from the Amazonia - Pacheco, Almir de Souza; Carvalho Xavier de Vasconcelos, Thomás; Reis, Adriel Matheus de Lima; da Silva, Carla Beatriz Amorim (DAT Journal, 2024)
The objective of the study is to value commercial Amazon fruits through Design. The research has an exploratory nature, in addition to a quali-quantitative approach. Using bibliographic review and questionnaire methods, data on fruits and the general population’s knowledge of these foods were obtained; to produce the illustrations, Péon (2003) methodology was used in an adapted form using its three stages: problematization, conception, specification. Throughout the research it was observed that these foods are unknown by the population as well as in academic works, in addition to being little used in the food base of people in cities. According to the results obtained, it’s feasible to say that there is a great potential for commercial, nutritional and visual applications of the fruits studied. Therefore, illustrations, icons and visual patterns were created for use in numerous future projects, helping to present these foods to the academic community and the population.